The effects of different types of bedding on the performance, skeletal and behavioral characteristics, hygienic and immunity conditions of suckling Holstein calves - Hosseini, S. M. J.; Tanha, T.; Maghsoodi, H. (Diponegoro University, 2021)
To investigate the effects of bedding types on the performance, skeletal and behavioral characteristics, health and immunity conditions of suckling Holstein calves, an experiment was conducted in a completely randomized design using 80 Holstein calves. The calves were distributed over 5 treatments and 4 replicates (each replicate included 2 male and 2 female calves). The 5 experimental treatments werechaff, straw, bagasse, sand, or mat. The results showed that the highest feed intake was related to the sand and chaff beddings and the highest weight gain (P<0.05) was found for the chaff, straw and sandbeddings . Withers height was highest and lowest for straw and mat treatments, respectively (P<0.05). The longest standing and resting times in calf behavior (P<0.05) were found for the sand and straw treatments, respectively. In cleanness, nose, eye, and joint scorings, the highest amount of con-tamination was related (P<0.05) to the mat and sand treatments . For immunity parameters, bagasse treatment showed the highest level of eosinophils (P<0.05) compared to the other treatments. Accord-ing to the results, it can be concluded that the straw bedding has better characteristics for growth, be-havior, and health of calves compared to the other beddings.